Impairment of assets disclosure by public listed companies in Malaysia - Shaari, Hasnah; Abdullah, Zaimah; Abdul Aziz, Saliza (Inderscience Publishers, 2013)
The main objectives of this study are to investigate the disclosure of assets impairment by Malaysian public companies and the compliance to FRS 136 impairment of assets.The study also tries to identify the demographical characteristics of companies who were affected by the adoption of this standard.100 companies which recognised impairment loss for the year 2003 were selected as our sample and the data were analysed using descriptive statistics.Our study revealed that the compliance to the disclosure requirements as per FRS 136 was unsatisfactory, except for two main requirements which were disclosing amount in the income statement and the nature of assets. The study also documented that property, plant and equipment (PPE) represent the highest tendency of non–current assets subjected to impairment loss.Indeed, the analysis also revealed that companies which poses large amount of PPE recognised high impairment loss than companies that carry small size of PPE.